Peer Communication on Sex and Sexual Health among youths: a case of Debre Berhan University, Ethiopia - Gezahegn, Takele; Birhanu, Zewdie; Aman, Mamusha; Dessalegn, Muluken; Abera, Asmamaw; Nyagero, Josephat (PanAfrican Medical Journal, 2016)
Introduction: friends are considered an important source of advice and information about sex. Conversations about sex among young people tend to generate norms that influence positive or negative pressure on individuals to conform to group standards. The aim of the study was to explore peer communication on sex and sexual health. Methods: grounded theory qualitative study design was employed using focus group discussions and participant observation. Participants were selected using criterion purposive sampling. Semi-structured guides and checklists were used as data collection tools. Information was audio-recorded and transcribed verbatim and uploaded to ATLAS.ti 7 software for coding. Data collection and analysis were undertaken simultaneously using constant comparative analysis. Results: students talked with peers and sexual partners about sex more than sexual health issues. Common places of talk included dormitory, begtera (near dorm where students meet), and space (reading rooms). Whereas, time of talk, either in a group or with just their close friends or sex partners, included during training, evening and weekend time, during walking together, and break time. Students used verbal and non-verbal and formal and informal communication styles. Conclusion: the content, place, and time for discussions about sex were influenced by gender, social-cultural norms (e.g. religion), rural vs urban living, and the occurrence of sexual health issues (e.g, sexually-transmitted infections or unwanted pregnancies). Priority should be given to designing audience-specific strategies and messages to promote discussions about sex and to encourage safe sexual practices. Primary target groups should include female and rural students, who are predisposed to risky sexual behavior.
The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
This article is published as part of the supplement “Strengthening health systems in communities: the experiences of AMREF Health Africa”
Keywords: Debre Berhan university; Peer communication; Sexual health talk; Grounded theory